2023
DOI: 10.1039/d2ra07954b
|View full text |Cite
|
Sign up to set email alerts
|

Ni loaded SnS2 hexagonal nanosheets for photocatalytic hydrogen generation via water splitting

Abstract: Schematic of photocatalytic H2 generation using Ni/SnS2 nanosheets along with the energy levels of SnS2 and Ni nanostructures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…The XRD spectra of all three samples of SnS 2 (Sn1, Sn2, and Sn3) possess a hexagonal structure, with the prominent peaks corresponding to SnS 2 , as reported in the literature. 36,37 From the XRD spectra of Sn 2 , it is clear that there exists a growth in the (001) direction of the lowest peak position (2θ < 10°). Thus, Sn 2 exhibits a refined structure with less impurity peaks when the composition is optimized with a Sn to S ratio as 1:2.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD spectra of all three samples of SnS 2 (Sn1, Sn2, and Sn3) possess a hexagonal structure, with the prominent peaks corresponding to SnS 2 , as reported in the literature. 36,37 From the XRD spectra of Sn 2 , it is clear that there exists a growth in the (001) direction of the lowest peak position (2θ < 10°). Thus, Sn 2 exhibits a refined structure with less impurity peaks when the composition is optimized with a Sn to S ratio as 1:2.…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalytic hydrogen generation study of prepared Ni@TiO 2 nanopowders was performed using water splitting technique by following previously reported procedure. 60 For this experiment, in-house designed 100 ml capacity quartz glass reactor was employed which was sealed with the septum for collecting the evolved H 2 with the help of a gas tight syringe. This water splitting mediated evolved hydrogen can then be applied to gas chromatogram (Shimadzu: Model GC 2014) for quantitatively analysing its production.…”
Section: Methodsmentioning
confidence: 99%
“…At higher concentration electroless nickel plating is intense which might be blocking the surface of TiO 2 which is responsible for lowering the surface area. 60,79…”
Section: Microstructural Study By Fetemmentioning
confidence: 99%
“…Various reports have shown that SnS 2 can be utilized in numerous photocatalytic applications, such as hydrogen production, 31–34 wastewater treatment, 35–39 antibacterial and antifungal activity, 40–43 and air purification. 44 For example, Yu et al 45 first reported the photocatalytic hydrogen production of SnS 2 nanosheets under solar light simulation with H 2 evolution activity of 1.06 mmol h −1 g −1 .…”
Section: Introductionmentioning
confidence: 99%